2007
DOI: 10.1002/adma.200602460
|View full text |Cite
|
Sign up to set email alerts
|

Homeotropic Alignment of Columnar Liquid Crystals in Open Films by Means of Surface Nanopatterning

Abstract: Columnar liquid crystals (LCs) are reported to align spontaneously homeotropically—that is, orthogonally to the surface (see figure and inside cover)—on a glass surface covered with a layer of poly(tetrafluoroethylene) transferred by friction (rubbing). This strategy for producing macroscopic monodomains of homeotropically aligned LCs may find important applications in the fabrication of LC‐based organic solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 26 publications
4
62
1
Order By: Relevance
“…Such a morphology has already been monitored by atomic force microscopy for the mesogen 1a in its soft crystal phase. [15] In order to substantiate the chiral supramolecular order of the chromophores, circular dichroism (CD) was studied for compound 2b in solution and thin films (Fig. 2).…”
Section: Communicationmentioning
confidence: 99%
“…Such a morphology has already been monitored by atomic force microscopy for the mesogen 1a in its soft crystal phase. [15] In order to substantiate the chiral supramolecular order of the chromophores, circular dichroism (CD) was studied for compound 2b in solution and thin films (Fig. 2).…”
Section: Communicationmentioning
confidence: 99%
“…Such structures are potential candidates for FETs owing to the fact that an excellent planar alignment of columns can be observed for this mesogen family. [10,75] It is even more appealing to prepare Hekates with different arms and confine chromophores to a specific space in the column by nanosegregation of the attached incompatible chains. This could be recently demonstrated for an oligobenzoate with a naphthalene arm decorated with semi-perfluorinated chains.…”
mentioning
confidence: 99%
“…Zimmermann et al first reported the planar orientation of a triphenylene DLC in its hexagonal plastic columnar phase by spin coating the material onto a PTFE alignment layer [108]. Uniaxial "in-plane" orientation of columnar phase was also achieved in HBC, phthalocyanine, pyrene, and benzoperylene derivatives by spin-casting the LC material onto a PTFE orientation layer [109][110][111]. Homeotropic alignement on the substrate can also be obtained by deposition of dilute solution of discotic molecules onto MoS 2 or highly oriented pyrolytic graphite, as reported for discotic triphenylenes, hexaazatriphenylene and HBCs [112][113][114].…”
Section: Surface Treatmentmentioning
confidence: 97%